2018
DOI: 10.1007/s10867-018-9484-9
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity impact of fenvalerate on the gill tissue of Oreochromis mossambicus with respect to biochemical changes utilizing FTIR and principal component analysis

Abstract: The use of pesticides in agriculture can make their way into the earth and wash into the amphibian system causing ecological stress. This study aims to understand the changes occurring in gill tissues as a result of fenvalerate exposure using Fourier-transform infrared spectroscopy. The intensity ratio of the selected bands I/I I/I, and I/I measures changes in proteins, lipids, and carbohydrates. Curve-fitting analysis was performed in the selected band region to analyze the quantitative changes of proteins, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 43 publications
3
3
0
1
Order By: Relevance
“…The further antiparallel β sheet was formed and an increase in band area 9-12% was observed with respect to control. This change in the secondary structure is in agreement with our earlier studies using FTIR on fish tissues [17]. Similar results of a decrease in the protein profile exposed to effluent toxicity of Channa punctatus (Bloch) were reported by Maruthi and Subba Rao [43].…”
Section: Ftir Self Deconvolution Deduced By Curve Fitting Analysis In the Amide I Regionsupporting
confidence: 92%
See 1 more Smart Citation
“…The further antiparallel β sheet was formed and an increase in band area 9-12% was observed with respect to control. This change in the secondary structure is in agreement with our earlier studies using FTIR on fish tissues [17]. Similar results of a decrease in the protein profile exposed to effluent toxicity of Channa punctatus (Bloch) were reported by Maruthi and Subba Rao [43].…”
Section: Ftir Self Deconvolution Deduced By Curve Fitting Analysis In the Amide I Regionsupporting
confidence: 92%
“…The bands rise at ~ 3013 cm −1 which indicates the presence of HC=CH group olefinic molecules. This band is used as a varying measure of degrees of unsaturation of phospholipids [17]. Lipids give rise to a number of absorption in FTIR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that toxicity due to tannery effluent influences metabolic pathways of Oreochromis mossambicus and the biochemical studies utilizing FTIR can fill in as incredible biomarkers of tannery effluent contamination. Similar results were observed in Cirrhinus mrigala and Oreochromis mossambicus treated with heavy metals and pyrethroids respectively (Karthikeyan et al, 2012;Velmurugan et al, 2018). It is observed from that decrease in muscle fat was observed due to tannery treatment and the increase in fat noted after supplementation with feed treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Among different techniques, Fourier transform-infrared (FTIR) spectroscopy, a form of vibrational spectroscopy, is one common analytical platform used in metabolic fingerprinting. It has been successfully applied to differentiate functional biochemical groups in the liver of fish exposed to different rearing conditions 11 , 12 , to determine the changes caused by spoilage in gilthead seabream 13 and salmon 14 , and to identify alterations provoked by toxic chemicals, in rainbow trout 15 , 16 , rohu 17 , 18 , Mozambique tilapia 19 and catfish 20 . Furthermore, FTIR spectroscopy was also applied to assess cod liver oil quality 21 and characterize hake lipids and lipid changes during frozen storage 22 .…”
Section: Introductionmentioning
confidence: 99%
“…No reference has been found in the literature regarding the use of FTIR spectroscopy to investigate the metabolic alterations in farmed fish induced by everyday aquaculture production stressors. However, previous studies on the effects of stressful conditions in algae 27 , yeast 28 , bacteria 29 and fish toxicology 19 demonstrate the potential of its application in this field. One great advantage of this spectroscopic technique is its ability to provide a broad outlook on fish metabolism without any preconceptions.…”
mentioning
confidence: 99%